Polański i symulacje. Na marginesie tekstu Ewy Mazierskiej "Roman Polański (i inni) przed sądem" - Tomczyk-Jarzyna, Izabela (Załącznik Kulturoznawczy, 2023)
Polanski and Simulations: A Few Remarks on Ewa Mazierska’s essay “Roman Polanski (and Others) on Trial” The text is a commentary on the article by Ewa Mazierska “Roman Polanski (and Others) on Trial.” Using Baudrillard’s concept of simulation, the author shows that discussions on Polanski’s personal conduct do not lead to finding meaning.